DAMPAK FAKTOR LINGKUNGAN TERHADAP KETAHANAN PANGAN RUMAH TANGGA PETANI KARET DI KABUPATEN KUANTAN SINGINGI - Iqbar Mahendra; Aslim Rasyad; Tengku Nurhidayah (Program Pascasarjana Universitas Riau, 2019)
This study aimed to analyze environmental factors on household food security of rubber farmers in Kuantan Singingi Regency. The study was using survey method with multi-stage cluster random sampling technique. The results of the study indicate that the food security status of rubber farmers in Kuantan Singingi Regency were not secure. It were caused by very low households income. The statistical analysis showed that the components of access to transportation and access to health facilities were significantly influence on household food security. The coefficient of access to transportation and access to health facilities were 127.72 (p = 0.0008) and 114.90 (p = 0.01), respectively. Based on the results of stepwise analysis, access to transportation and access to health facilities were good parameters as dominant factors determining on household food security of rubber farmers.